2015
DOI: 10.1016/j.molcel.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the CRISPR-Cas RNA Silencing Cmr Complex Bound to a Target Analog

Abstract: In prokaryotes, Clustered regularly interspaced short palindromic repeat (CRISPR)-derived RNAs (crRNAs), together with CRISPR-associated (Cas) proteins, capture and degrade invading genetic materials. In the type III-B CRISPR-Cas system, six Cas proteins (Cmr1-Cmr6) and a crRNA form an RNA silencing Cmr complex. Here we report the 2.1 Å crystal structure of the Cmr1-deficient, functional Cmr complex bound to single-stranded DNA, a substrate analog complementary to the crRNA guide. Cmr3 recognizes the crRNA 5' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
169
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(189 citation statements)
references
References 53 publications
14
169
0
Order By: Relevance
“…This allows sharing of crRNA processing pathways, with the mature crRNAs ultimately getting loaded onto specific effector complex. Type III system displays two kinds of effector complexes -Csm (Type III-A/D) or Cmr (Type III-B/C) (Hale et al, 2009;Zhang et al, 2012; Hatoum-Aslan et al, 2013;Rouillon et al, 2013;Tamulaitis et al, 2014;Zhang et al, 2016), which show distant relationship with Type I effector complex (Rouillon et al, 2013;Osawa et al, 2015;Taylor et al, 2015).…”
Section: Type I and Type Iii Crispr Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows sharing of crRNA processing pathways, with the mature crRNAs ultimately getting loaded onto specific effector complex. Type III system displays two kinds of effector complexes -Csm (Type III-A/D) or Cmr (Type III-B/C) (Hale et al, 2009;Zhang et al, 2012; Hatoum-Aslan et al, 2013;Rouillon et al, 2013;Tamulaitis et al, 2014;Zhang et al, 2016), which show distant relationship with Type I effector complex (Rouillon et al, 2013;Osawa et al, 2015;Taylor et al, 2015).…”
Section: Type I and Type Iii Crispr Systemsmentioning
confidence: 99%
“…However, in case of type III systems, pre-CRISPR transcript is processed by Cas6 in solitude and not as part of the effector complex (Carte et al, 2008; Carte et al, 2010;Wang et al, 2011;Shao and Li, 2013;Shao et al, 2016; Makarova et al, 2017a). Further, Cas6/III does not become a constituent of interference complex (Hale et al, 2009;Zhang et al, 2012;Rouillon et al, 2013;Spilman et al, 2013; Benda et al, 2014;Staals et al, 2014;Osawa et al, 2015;Taylor et al, 2015; Makarova et al., 2017a), with the exception being Csm/III-A complex from Streptococcus thermophilus that shows weak transient interactions with Cas6 (Tamulaitis et al, 2014). This possibly grants Cas6/ III the flexibility required to associate with multiple subtypes that potentially differ at the interference stage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electron microscopy data and protein crystallographic studies have revealed in detail the composition and function of the Cascade [22][23][24][25][26] and the Cmr crRNP complexes [17,27]. Furthermore, electron microscopy and MS data have defined the Csm crRNP complex from Sulfolobus solfataricus, which is formed by up to seven different proteins [28] and a homologous complex in Thermus thermophilus that consists of five different proteins: Csm1-5 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, electron microscopy and MS data have defined the Csm crRNP complex from Sulfolobus solfataricus, which is formed by up to seven different proteins [28] and a homologous complex in Thermus thermophilus that consists of five different proteins: Csm1-5 [18]. Cmr, Csm and Cascade complexes show overall structural similarity because they are formed by structurally and functionally related subunits [27,28]. In the present study, aiming to obtain more more information about the Csm crRNP complex, we cloned, expressed, purified, crystallized and solved the structure of the Csm2 protein of Thermotoga maritima MSB8.…”
Section: Introductionmentioning
confidence: 99%